1999
DOI: 10.1007/s002640050350
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow of the gluteus medius muscle

Abstract: We investigated the effects of subperiosteal dissection on blood flow in the gluteal medius muscle in adult rabbits using the hydrogen washout technique. After the control blood-flow rate was determined, 8 rabbits were separated into 2 groups according to the direction of the dissection. The gluteal medius muscle was dissected from the iliac crest in the proximal-distal direction in 10 hips. In another 6 hips, the greater trochanter was osteomised and the gluteus medius muscle was dissected from the ilium in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…33 The artery and nerve are at risk of injury during lateral approaches to the hip, and this may contribute to hip abductor tendon failure postoperatively. 12,33,34 Interestingly, the superior gluteal artery sends branches into the trochanter through the insertion of gluteus medius and minimus, making it an important supplier to the muscle, tendon and the trochanter. 32,35 The branches of the superior gluteal artery supplying the gluteus minimus also contribute to the supply of the hip capsule and the acetabular region.…”
Section: Anatomymentioning
confidence: 99%
“…33 The artery and nerve are at risk of injury during lateral approaches to the hip, and this may contribute to hip abductor tendon failure postoperatively. 12,33,34 Interestingly, the superior gluteal artery sends branches into the trochanter through the insertion of gluteus medius and minimus, making it an important supplier to the muscle, tendon and the trochanter. 32,35 The branches of the superior gluteal artery supplying the gluteus minimus also contribute to the supply of the hip capsule and the acetabular region.…”
Section: Anatomymentioning
confidence: 99%
“… 22) The results of our previous study, examining the effects of subperiosteal dissection on blood flow in an animal model, suggested that the mid-portion of the gluteus medius muscle receives much of its blood from the ilium. 23) Extensive dissection of the abductors from the outer aspect of the pelvis for the sake of iliac osteotomy may cause ischemic insult to the functional integrity of the muscle, and result in persistently poor postoperative abductor function.…”
Section: Factors Affecting Postoperative Outcomesmentioning
confidence: 99%